2014
DOI: 10.1111/ijac.12301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrodeposition Parameters on the Microstructure and Corrosion Behavior of ‎DCPD Coatings on Biodegradable Mg–Ca–Zn Alloy

Abstract: In this study, DCPD (Brushite, CaHPO4.2H2O) coatings were prepared on the surface of a Mg–Ca–Zn alloy using different current density (0.15–1.2 mA/cm2) and deposition time (5–90 min). The results revealed that DCPD with needle‐like morphology was observed for the current density between 0.15 and 0.4 mA/cm2‎, whereas ‎plate‐like morphology was obtained at current density above 0.8 mA/cm2. The results showed that surface roughness increased with increasing current density. The lowest corrosion rate of 0.14 mm/ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
0
11
0
1
Order By: Relevance
“…The produced CaO could expand during its formation, disintegrating the DCPD coating and generating craters. Bakhsheshi‐Rad et al also reported volcano‐like sites in a DCPD coating formed galvanostatically at current density of 0.8 mA/cm 2 . However, they did not reveal the composition and microstructure of the crater.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The produced CaO could expand during its formation, disintegrating the DCPD coating and generating craters. Bakhsheshi‐Rad et al also reported volcano‐like sites in a DCPD coating formed galvanostatically at current density of 0.8 mA/cm 2 . However, they did not reveal the composition and microstructure of the crater.…”
Section: Resultsmentioning
confidence: 93%
“…Current density is a key factor to influence the phase composition and microstructure of a CaP coating . Studies have shown that current density can affect the weight and thickness of the coating deposited by a galvanostatic electrodeposition process. Currently, most of the available studies are focused on the characterization and evaluation of coatings deposited under given conditions, either galvanostatically or potentiostatically, without considering the detailed coating process or the dependence of the process on coating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the inner corrosion layer was formed and thought to be responsible for the deterioration of the corrosion. Comparatively, Wang et al [42] and Hamid Reza et al [43] fabricated the Ca-P coating on the as-cast Mg-Zn-Ca alloy via electrodeposition method and similar inner corrosion layer was also found between the coating and substrate. It was found that the corrosion products layer was thin and acted as a transition layer which was helpful for the improvement on the interfacial bonding strength.…”
Section: Discussionmentioning
confidence: 99%
“…4 For instance, in a study by Abdolrazek et al, 5 PMMA was blended with PCL as a biocompatible and cost-effective polymer through casting method to enhance its structural and physical properties. [13][14][15] In this respect, Chen et al 16 demonstrated that the addition of 10 to 50 wt.% silicate-based ceramic (akermanite; Ca 2 MgSi 2 O 7 ) to PMMA resulted in escalating apatite formation ability and mechanical properties of pure PMMA. However, PMMA-PCL-based cements suffer from low bioactivity which results in the formation of a fibrous layer between bone and cement, hence leading to implant failure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies [10][11][12] verified that the addition of glass-ceramics containing Si, Ca, and Mg and silicate-based ceramic to the PMMA bone cement increases their bioactivity owing to the release of the Mg, Si, and Ca ions in the surrounding environment. [13][14][15] In this respect, Chen et al 16 demonstrated that the addition of 10 to 50 wt.% silicate-based ceramic (akermanite; Ca 2 MgSi 2 O 7 ) to PMMA resulted in escalating apatite formation ability and mechanical properties of pure PMMA. Among the Si-based bioceramics, baghdadite (BAGH) (Ca 3 ZrSi 2 O 9 ) with mechanical characteristics close to cortical bone and greater osteogenic properties and bioactivity has presented higher capability compared to the Ca-P bioceramics for orthopedic applications.…”
Section: Introductionmentioning
confidence: 99%